Efeito Da Velocidade De Secagem Sobre A Emergência E Vigor De Sementes De Pupunha (Bactris Gasipaes Kunth) - Ferreira, Sidney Alberto do Nascimento (Acta Amazonica, 2020)
Peach palm (Bactris gasipaesKunth, Palmae) seeds loose their viability rapidly if their humidity content is reduced, consequently reducing transport and seed storage success. To studying the effect of drying velocity, seeds were maintained in the following conditions: a) on the laboratory bench; b) in a desiccator jar with 1 part silica gel to 1 part seeds by weight; c) in a desiccator jar with 2:1 silica gel: seeds for 10 days, samples were taken every 2nd day for germination tests and humidity determinations. The results indicate that viability and vigour of the seeds are affected by both: the humidity content and the velocity of drying. Slower drying is more favorable for maintaining seed viability and vigour.